The Type Ia Supernova and Asymptotic Giant Branch Stellar Ejecta-regulated Interstellar Medium of Massive Galaxies - Rajsekhar Mohapatra; Eliot Quataert; Drummond Fielding; Minghao Guo (The Astrophysical Journal)
Observations and theory suggest that Type Ia supernovae (SNIa) heating and mass loss from asymptotic giant branch (AGB) stars play a crucial role in the interstellar medium (ISM) of massive galaxies. We perform 3D hydrodynamic simulations of the central few kiloparsecs of massive galaxies, including radiative cooling and mass and energy injection from AGB winds and SNIa (resolving each SNIa remnant, a few ×10 pc in size), excluding black hole feedback. We study systems with different initial core thermodynamic profiles, focusing on NGC 1399. Our fiducial simulation reproduces its observed density and entropy profiles well. Over 100 Myr, two steady-state profiles emerge, depending on the inner circumgalactic medium (CGM) pressure and the ratio of Ia heating to cooling: (i) if SNIa heating is less than cooling, a cooling flow develops; (ii) if SNIa heating is comparable to or exceeds cooling, SNIa heating drives a slow subsonic outflow of AGB ejecta, with black hole accretion at small radii. This outflow, pressure-confined by the CGM, adapts the ISM to the CGM properties: a low-entropy CGM results in a dense, low-entropy ISM with higher black hole accretion, while a high-entropy CGM leads to a less dense, high-entropy ISM with lower accretion. This suggests that the AGB-SNIa-regulated ISM connects CGM and galaxy scales, potentially influencing black hole feedback in massive halos. Approximate methods of modeling Ia heating, such as clustered SNIa and smoothly distributed heating, produce unrealistic ISM profiles over 100 Myr, highlighting the importance of resolving SNIa in simulations.